Policy Formulation In Legal Protection Of Working Children Outside A Working Relationship - Ujang Charda S (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2021)
Legal protection for child labor is still different for children who work for an employer and for children who work for themselves. This is not in line with the principles of legal protection, the goals of labor law, the nature of labor law, and the legal scope of employment. whose goals are not only to protect the interests of workers before, during, and after a period of work, but also to make sure that everyone has a job and can make a decent living for all of humanity without any discrimination in the way work relations are set up and run. The research method is descriptive-analytical with a normative-legal approach through library research and field research, with techniques for gathering data through library research. Then the data were analyzed through a qualitative normative method without using numbers and mathematical formulas. Based on the results of the study, it shows that the regulation of children who work outside of an employment relationship has implications for the responsibility of the state in providing legal protection through planning the formulation of government policies that are not only focused on children who work in an employment relationship, but also on children who work outside of an employment relationship.